IMPACT OF ENACTMENT OF THE NEW PENAL CODE ON THE OFFENCE OF INTERNATIONAL HIGH RISK DRUG TRAFFICKING - Traian DIMA; Adrian HĂRĂTĂU (Challenges of the Knowledge Society)
The entry into force of the new Penal code has brought some changes on the offence of international high-risk drug trafficking. This study aims to analyze the impact of the new Penal Code, by changing the limits of punishment in the case of the international high-risk drug trafficking, had on this offence, in relation to other existing criminal provisions reffering to the high-risk drugs or very hihg-risk drugs.